Experimental and numerical study on multi-impact performance of pre-damaged beams strengthened with CFRP. (15th June 2023) - Zhang, Yafang; Duan, Libin; Liu, Hao; Lu, Juan; Huo, Yongjie
Highlights: A number of pre-damaged beams strengthened with CFRP were tested under multiple impact. The failure patterns are different under different CFRP strengthening methods. U-wrapping CFRP has better performance. A new FEM simulation for multi-impact was tested. Abstract: In this study, low-velocity impact loads were first applied to produce pre-damages in three reinforced concrete (RC) beams, followed by strengthening with carbon fiber reinforced plastic (CFRP) and reloading under multi-impact. Two strengthening types, say, in straight and U-wrapping ways, were considered in the tests to determine which type is more effective to resist impact load. Furthermore, a 3D nonlinear finite element model was established to compare the experimental results and hopefully to investigate deeply in exploring other reinforcement measures. The results show that cracks of beams with U-wrapping CFRP are mainly concentrated in the mid-span area, and the crack distribution range is significantly reduced compared with un-strengthened RC beams or beams strengthened with straight CFRP. It can be concluded that CFRP can help to improve the performance of the pre-damaged beam, decrease the stiffness loss due to damage and enhance energy dissipation. The deformation recovery capacity of CFRP-strengthened beams is also enhanced under multi-impact, particularly in U-wrapping CFRP beams. In addition, the multi-impact performance in terms of the cracking pattern, impact force, and displacement history can be well visualized in the numerical simulation.